RANCANG BANGUN APLIKASI MENGENAL JENIS KECERDASAN DAN BAKAT SISWA BERBASIS ANDROID - Tina Puspita; siswanto siswanto; Ricky Zulfiandry (UNIVED Press, 2022)
ABSTRACT The State 17 Junior High School in Bengkulu City is one of the junior high schools in Bengkulu Province, the same as junior high schools in general whose education is taken within 3 years of study, starting from grades VII and IX. This school is located at Wr. Supratman Street, Pematang Governor, Muara Bangkahulu District. The subject of this research is the design of applications to recognize the intelligence and talent of Android-based students on Android devices. While the research subjects were students of class 1X State Junior High School 17 Bengkulu City. State Junior High School 17 Bengkulu City for class 1X consists of 2 classes, with a total of 64 students. The large number of students taken for testing refers to a statement that explains that